Comparative genome hybridization suggests a role for NRXN1 and APBA2 in schizophrenia - George Kirov; Dilihan Gumus; Wei Chen; Nadine Norton; L. Georgieva; Murat Sarı; Michael O’Donovan; Fikret Erdogan; Michael J. Owen; H.-H. Ropers; Reinhard Ullmann (2007)
Copy number variations (CNVs) account for a substantial proportion of human genomic variation, and have been shown to cause neurodevelopmental disorders.We sought to determine the relevance of CNVs to the aetiology of schizophrenia (SZ).Whole-genome, high-resolution, tiling path BAC array comparative genomic hybridization (array CGH) was employed to test DNA from 93 individuals with DSM-IV SZ.Common DNA copy number changes that are unlikely to be directly pathogenic in SZ were filtered out by comparison to a reference dataset of 372 control individuals analyzed in our laboratory, and a screen against the Database of Genomic Variants.The remaining aberrations were validated with Affymetrix 250K SNP arrays or 244K Agilent oligo-arrays and tested for inheritance from the parents.A total of 13 aberrations satisfied our criteria.Two of them are very likely to be pathogenic.The first one is a deletion at 2p16.3 that was present in an affected sibling and disrupts NRXN1.The second one is a de novo duplication at 15q13.1 spanning APBA2.The proteins of these two genes interact directly and play a role in synaptic development and function.Both genes have been affected by CNVs in patients with autism and mental retardation, but neither has been previously implicated in SZ.